2001
DOI: 10.1111/j.1749-6632.2001.tb03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Platelet‐Endothelial Cell Adhesion Molecule‐1 (PECAM‐1) Gene, Asn563Ser and Gly670Arg, Associated with Myocardial Infarction in the Japanese

Abstract: We examined three missense polymorphisms of platelet‐endothelial cell adhesion molecule‐1 (PECAM‐1), Val125Leu, Asn563Ser, and Gly670Arg, in 136 Japanese patients with myocardial infarction and 235 healthy Japanese controls. We found that these polymorphisms were in linkage disequilibrium with each other and that frequencies of 125Leu, 563Ser, and 670Arg alleles were significantly increased in patients compared with controls (0.522 vs 0.447, p= 0.048; 0.585 vs 0.502, p= 0.030; and 0.577 vs 0.492, p= 0.032, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 37 publications
3
43
0
1
Order By: Relevance
“…However 125Leu variant suggested to modulate platelet activation leading to increased risk of MI [18] was more associated with MI patients (0.57) as compared to controls (0.504). Similar finding is also reported by Sasaoka et al [14] in MI. In our study there was significant increase in sPECAM-1 levels in MI patients at acute event (MI-Group-1) as compared to treated patients (MI-Group-2).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However 125Leu variant suggested to modulate platelet activation leading to increased risk of MI [18] was more associated with MI patients (0.57) as compared to controls (0.504). Similar finding is also reported by Sasaoka et al [14] in MI. In our study there was significant increase in sPECAM-1 levels in MI patients at acute event (MI-Group-1) as compared to treated patients (MI-Group-2).…”
Section: Discussionsupporting
confidence: 92%
“…Against these reports Gardemann et al [11] in German population and Elrayees et al [12] in British population did not find Leu125Val gene polymorphism of PECAM-1 as an independent risk factor of CAD. A study by Listi et al [13] in population from Sicily (Italy), reported no significant association of this polymorphism with MI while Sasaoka et al [14] in Japanese population have reported increased 125Leu allele frequency (0.52 vs. 0.447, P = 0.048) in MI patients as compared to controls.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations